Education and Simulation of Range of Motion (ROM) for Caregivers to Improve the Quality of Life of Older People in the Community - Suyasa, I Gede Putu Darma; Sutini, Ni Kadek; Israfil, Israfil; Indrayani, Ni Luh Dwi; Agustini, Ni Luh Putu Inca Buntari; Oka Putra, I Nyoman Trisna Oka Putra (Ahmar Metakarya: Jurnal Pengabdian Masyarakat, 2025)
The aging process has caused various health problems, including limited physical mobility due to muscle weakness, joint stiffness, and certain chronic disease conditions. Efforts to maintain the health of older people can be done through Range of Motion (ROM) exercises, with the family as caregivers having an essential role in doing so. This community service activity aims to improve the knowledge of elderly caregivers by providing education and simulations on ROM exercises for older people. A total of 41 caregivers from Melinggih Village, Gianyar Regency and Pedungan Village, Denpasar City were involved in this activity in March 2025. The activity was carried out using the education and simulation method, with stages using the PARE (Preparation, Action, Reflection, and Evaluation) approach. The results of the Wilcoxon statistical test obtained a p-value < 0.001 with Z = - 3.65, which showed a significant difference in the level of caregiver knowledge about ROM exercises in older people before and after the activity. Good knowledge increased from 63% to 100%, and poor knowledge decreased from 31.7% to 0%. This shows that community service activities with education and simulation methods have successfully increased caregivers' knowledge and practical abilities in performing ROM exercises for older people. ROM exercises can be an easy choice for caregivers as an effective way to maintain the health of older people in the community, support long-term care programs, and thus improve the quality of life for the older people in the community.